2019
DOI: 10.1001/jamainternmed.2018.7729
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the USPSTF Recommendations on Prevention of Perinatal Depression—Opportunities and Challenges

Abstract: In this issue of JAMA, the United States Preventive Services Task Force (USPSTF) recommends that clinicians refer pregnant and postpartum (ie, perinatal) persons who are at increased risk for depression to counseling interventions (B recommendation). 1 Based on a systematic review of 50 studies, 2 the USPSTF "concludes with moderate certainty that providing or referring pregnant or postpartum women at increased risk to counseling interventions has a moderate net benefit in preventing perinatal depression." 1 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Highlighting the need for such studies is the recent recommendation by the United States Preventive Services Task Force to refer all women at increased risk of perinatal depression to counseling services. Implementing this recommendation will place a tremendous burden on the health care system, which already has a shortage of mental health care providers [69][70][71][72][73][74]. Thus, the findings from this study support the need for pragmatic trials, which will provide evidence on the effectiveness of implementing low-cost, technology-based programs for women with moderate to moderately severe PPD symptoms, which are necessary for improving the health of families.…”
Section: Discussionmentioning
confidence: 56%
“…Highlighting the need for such studies is the recent recommendation by the United States Preventive Services Task Force to refer all women at increased risk of perinatal depression to counseling services. Implementing this recommendation will place a tremendous burden on the health care system, which already has a shortage of mental health care providers [69][70][71][72][73][74]. Thus, the findings from this study support the need for pragmatic trials, which will provide evidence on the effectiveness of implementing low-cost, technology-based programs for women with moderate to moderately severe PPD symptoms, which are necessary for improving the health of families.…”
Section: Discussionmentioning
confidence: 56%
“…48 Interventions such as interpersonal therapy, cognitive behavioural therapy, non-directive counselling, and peer and partner support aim to build social support and lead to behavioural changes that enhance coping and reduce distress. 49,50 Ideally, prophylactic measures in terms of prospective support for all pregnant and newly delivered mothers should be offered, and would most likely result in reducing disease severity and burden for women and families. However, large-scale population-based interventions often confer a substantial load on the healthcare system.…”
Section: Resultsmentioning
confidence: 99%
“…Though PPD screening is recommended by American College of Obstetricians and Gynecologists (2018) and the United States Preventive Services Task Force (Felder, 2019), few participants felt that PPD had been addressed well during pre- and postnatal visits. Although early prenatal care can help mitigate some of the effects of substance use during pregnancy, studies have found that women in rural areas face multiple challenges to receiving care such as transportation concerns and fear of judgment by health care providers (Benoit et al, 2015; Kramlich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%